White-Box Testing of Behavioral Web Service Contracts With Pex - Tillmann, Nikolai; Halleux, Jonathan "Peli" de (TAV-WEB '08: Proceedings of the 2008 workshop on Testing, analysis, and verification of web services and applications, 2008)
A web service exposes a public API that can be accessed by potentially hostile clients over the internet. Pex, a white-box test generation tool for .NET, can automatically create test inputs that cover comer cases of a web service implemented in .NET, simulating a malicous attacker.